Differences in acute physiological response to a Qigong exercise among middle-aged adults with varying durations of Qigong practice - Sun, Jingyu; Zhang, Zhangxiaohe; Zhao, Rongji; Jia, Nannan; Chen, Jiajia; Qin, Duran; Wang, Jing; Zhang, Zhengyi; Yang, Hao; Lu, Tianfeng; Cicchella, Antonio; Chen, Tao (Frontiers in Physiology, 2026)
BackgroundQigong combines physical movement, breath control, and mental focus, offering potential benefits for healthy aging. Since physiological decline begins in midlife, this stage is critical for preventive intervention. The purpose of this study was to investigate the differences in acute physiological responses, including autonomic (heart rate variability) and respiratory indicators, during a single session of combined Yijinjing and Liuzijue Qigong in middle-aged adults with varying durations of practice experience (≥4 years vs. ≤6 months).MethodsForty adults aged 40 to 59 were included and divided into two groups based on Qigong exercise experience: an experienced group (n = 20) with ≥4 years of practice, and an inexperienced group (n = 20) with <6 months. All participants performed 20 min of fitness Qigong, following prerecorded tapes to standardize pace and posture sequence. Heart rate variability (HRV) and respiration were measured using the Biofeedback 2000x-pert system before, during, and after the session.ResultsSignificant Group × Time interactions were found for SDNN (F = 5.58, p = 0.012), RMSSD (F = 20.52, p < 0.001) and LF (F = 5.47, p = 0.025). Between-group comparisons indicated that experienced group had slightly higher SDNN at rest (p = 0.039) and significantly higher RMSSD during the recovery phase (p < 0.001); no other between-group differences emerged at other phases. There was a significant Group × Time interaction for abdominal breathing depth (F = 3.911, p = 0.024) and thoracic breathing frequency (F = 4.956, p = 0.016). Between-group comparisons revealed deeper abdominal breathing during exercise and slower thoracic breathing during recovery in the experienced group.ConclusionMiddle-aged adults with prolonged practice of Qigong exercise have improved HRV compared to those in the inexperienced group, and these improvements may be achieved through a combination of breathing adjustments with mental focus and relaxation.